2007
DOI: 10.1161/01.hyp.0000258405.25330.80
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Dimethylarginine and Reduced Nitric Oxide Bioavailability in Young Black African Men

Abstract: Abstract-Black Africans have a higher incidence of cardiovascular disease than white Europeans. We explored potential mechanisms of this excess risk by assessing endothelium function, inflammatory status (C-reactive protein), oxidative stress (isoprostane-F2␣), and plasma asymmetrical dimethyl arginine (ADMA; an endogenous competitive inhibitor of NO synthase) in each ethnic group. 1 This in part may be explained by an increased prevalence and severity in blacks of some risk factors for atherosclerosis. In pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
54
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 32 publications
4
54
1
Order By: Relevance
“…The results of our analysis are consistent with previously described interactions of these mechanisms in an epidemiological context. 19,29,33,58,59 In addition, our results contribute to an understanding of the metabolic role of L-arginine in the differential prevalence of hypertension in Africans and Caucasians.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The results of our analysis are consistent with previously described interactions of these mechanisms in an epidemiological context. 19,29,33,58,59 In addition, our results contribute to an understanding of the metabolic role of L-arginine in the differential prevalence of hypertension in Africans and Caucasians.…”
Section: Discussionmentioning
confidence: 69%
“…31,33 --36 Profiles of several other cardiovascular risk factors in the two ethnic groups also differ. For example, Melikian et al 33 reported that in a small study on black Africans (n ¼ 30) living in Europe, ethnicity predicted serum concentrations of ADMA. A decrease in the relative availability of NO may diminish endothelial function, potentially contributing to the higher prevalence of hypertension and cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…The strong relationship between ADMA and arterial stiffness observed in the African men could point to a different vascular mechanism in the development of cardiovascular disease previously seen in black African men (1,7). It is well known that compared to Caucasians, Africans disclose larger increases in aortic and peripheral PWV after smoking (30), they show no changes in the peripheral arterial response to exercise compared to Caucasians who show significant reductions (31), and their peripheral muscular arteries show increased PWV with diabetes, with no change in Europeans (32).…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, the increasing incidence of diabetes (5) in Africa will aggravate the severity of renal and cardiac damage caused by any given blood pressure (BP) level (1). Although a high prevalence of known modifiable risk factors for atherosclerotic disease and hypertensive heart disease is detected in black South African individuals (6), these conventional risk factors do not account for all of their increased risk (7). It is therefore imperative to identify additional markers that might explain their increased risk and may contribute to the early detection and prevention of vascular and metabolic abnormalities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation